Comparison of remifentanil concentrations with and without dexmedetomidine for the prevention of emergence cough after nasal surgery: a randomized double-blinded trial - Kim, Ha Yeon (BMC Anesthesiol, 2021)
BACKGROUND: Preventing emergence cough after nasal surgery is critical. Emergence cough can provoke immediate postoperative bleeding, which leads to upper airway obstruction. In the present study, we compared the effect-site concentration (Ce) of remifentanil to prevent emergence cough after propofol anesthesia for nasal surgery when remifentanil was or was not combined with dexmedetomidine. METHODS: Forty-seven patients with propofol-remifentanil anesthesia for nasal surgery were randomly assigned to a dexmedetomidine group (Group D, n = 23) or a saline group (Group S, n = 24). Group D and Group S were infused with dexmedetomidine (0.5 μg/kg) and saline, respectively, for 10 min before the completion of surgery. A predetermined Ce of remifentanil was infused until extubation. Remifentanil Ce to prevent cough in 50 and 95% of patients (EC(50) and EC(95)) was estimated using modified Dixon’s up-and-down method and isotonic regression. Hemodynamic and recovery parameters were recorded. RESULTS: The EC(50) of remifentanil Ce was significantly lower in Group D than in Group S (2.15 ± 0.40 ng/mL vs. 2.66 ± 0.36 ng/mL, p = 0.023). The EC(95) (95% CI) of remifentanil Ce was also significantly lower in Group D [2.75 (2.67–2.78) ng/mL] than in Group S [3.16 (3.06–3.18) ng/mL]. Emergence and recovery variables did not differ between the two groups. CONCLUSION: The remifentanil EC(50) to prevent cough after propofol-remifentanil anesthesia was significantly lower (approximately 19%) when a combination of remifentanil and 0.5 μg/kg dexmedetomidine was used than when remifentanil infusion alone was used in patients undergoing nasal surgery. Therefore, the Ce of remifentanil may be adjusted to prevent emergence cough when used in combination with dexmedetomidine. TRIAL REGISTRATION: ClinicalTrials.gov (NCT03622502, August 9, 2018).